Loss of Nicotinamide nucleotide transhydrogenase sensitizes embryos to ethanol-induced neural crest and neural apoptosis via generation of reactive oxygen species - Mazumdar, Rayna; Eberhart, Johann K. (Frontiers in Neuroscience, 2023)
Fetal alcohol spectrum disorders (FASD) are a continuum of birth defects caused by prenatal alcohol exposure. FASD are the most common environmentally induced birth defect and are highly variable. The genetics of an individual influence the severity of their FASD phenotype. However, the genes that sensitize an individual to ethanol-induced birth defects are largely unknown. The ethanol-sensitive mouse substrain, C57/B6J, carries several known mutations including one in Nicotinamide nucleotide transhydrogenase (Nnt). Nnt is a mitochondrial transhydrogenase thought to have an important role in detoxifying reactive oxygen species (ROS) and ROS has been implicated in ethanol teratogenesis. To directly test the role of Nnt in ethanol teratogenesis, we generated zebrafish nnt mutants via CRISPR/Cas9. Zebrafish embryos were dosed with varying concentrations of ethanol across different timepoints and assessed for craniofacial malformations. We utilized a ROS assay to determine if this could be a contributing factor of these malformations. We found that exposed and unexposed mutants had higher levels of ROS compared to their wildtype counterparts. When treated with ethanol, nnt mutants experienced elevated apoptosis in the brain and neural crest, a defect that was rescued by administration of the antioxidant, N-acetyl cysteine (NAC). NAC treatment also rescued most craniofacial malformations. Altogether this research demonstrates that ethanol-induced oxidative stress leads to craniofacial and neural defects due to apoptosis in nnt mutants. This research further supports the growing body of evidence implicating oxidative stress in ethanol teratogenesis. These findings suggest that antioxidants can be used as a potential therapeutic in the treatment of FASD.